Determinación de compuestos piretroides en muestras de aspirado gástrico por el método de cromatografía en capa fina que ingresan al laboratorio de química forense del departamento de criminalística de la policía judicial de chimborazo - Edison Hernán, Alcívar Arias (2013)
Pyrethroids is a group of chemicals that have insecticidal activity. It means they help to control pests. These chemicals may also affect directly people who handle these compounds. That is why this research aims to determine the presence of pyrethroid compounds in samples of gastric contents from cadavers that are taken to the morgue of the General Cemetery in the city of Riobamba, which was conducted in the Laboratory of Forensic Chemistry Judicial Police of the Province of Chimborazo, First, the behavior of the pyrethroid compound, its toxicokinetic, involving absorption, distribution, metabolism and elimination will be known. This process will help us to understand how danger this is for human beings, and then with the samples obtained liquid - liquid will be performed. This is a technique that will allow us to purify and extract the needed compound for our study. After, a necessary test is developed which is a thin layer chromatography. The application of a qualitative method will allow the identification of the pyrethroid compound, through a physical developer (VU lamp) and chemical developer(potassium permanganate 0.5 N) and then calculate its retention factors (Fr). These factors are useful to analyze positive results obtained in the research, thus it contributes to the medical examiner to determine the cause of death of an individual. This research will help directly, as a timely contribution to society that ignores the dangers of handling and use of these substances are risks for human beings.